Program Assessment and Evaluation for Continuous Quality Improvement - Sunitha, Gurram; Avanija, J. (Journal of Engineering Education Transformations, 2021)
Measurement of educational system/outcomes is a very complex, tedious and rigorous process. Immeasurable educational system/outcomes, means that the educational system is not properly understood or that the measurement system is not properly defined or benchmark measurement techniques are not yet developed. If educational system and its outcomes are not properly measured, then the educational system in itself is not properly understood, the goals of educational system are vaguely set and there is no process of review and refinement of quality of educational system. The intangibles of educational system must be clearly understood, well-defined and crisply measured to achieve the goals of outcome-based education and redirect the future of educational system. Measuring scholarship of knowledge in students and academic success of institutions is the key to deliver potentially skilled graduates to the society and the nation. Measurement of outcomes of education provides reliable insights for understanding the impact of education on stakeholders. This paper presents a model for measuring outcomes attainments for one-to-many model course outcome-program outcome mapping and also presents a sample of how to use assessment result s for continuous quality improvement.